Hayruddin Hızır el-Atûfî ve Keşşâf Haşiyesi / Khair al-Din Khidir al-Atufi and His Hashiya on al-Kashshaf - Tezcan, Tuğrul (Journal of History Culture and Art Research, 2018)
Abstract Al-Atufi, a scholar born in Merzifon witnessed the eras of Bayazid II, Selim I and Suleiman I and was employed as a tutor in the palace in the period of Bayazid II. He had long engaged in preaching through tafsir lessons in various mosques in İstanbul before he died there in 1541. He wrote commentaries in miscellaneous fields, such as tafsir, hadith, al-tibb al-nabawi, ta’bir al-ru’ya and logic. He authored three commentaries and a treatise interpreting a verse, namely Hashiya ala al-Kashshaf – from al-Naba’ to al-Nas, Hashiya ala Anwar al-Tanzil, and on al-Baidawi’s interpretation of a verse in al-Mulk: Risala fi Bayan Tafsir Qawlih Ta’ala ‘Fa-suhqan’ and Hisn al-Ayat al-Izam fi Tafsir Awail Sura al-An’am. Employing maani and bayan in his commentaries, al-Atufi successfully transformed the knowledge to gnosis. He displays the subtleties of the way from the cause to the effect regarding lugha, nahw and balagha. Similar characteristics of al-Atufi can be seen in his Hashiya ala al-Kashshaf. The comments made on what al-Zamakhshari touched briefly are occasionally meant to criticize. Al-Atufi quoted directly from al-Nasafi, al-Baidawi and so forth in tafsir, from al-Farra, al-Sakkaki and Ibn Juraij in lugha and from Ibn Abbas, Muqatil and others in riwaya. He levelled criticisms at some whose views quoted, within the scope of lugha. He referred to al-Zamakhshari as müsannif recounting his opinions with ‘qawluhu’. He used al-Zamakhshari’s way of interpretation: ‘said – I say’. Ignoring his views on the issues of faith, he expressed his own opinions writing a supplement. There he examined the most recited chapters in prayers and elucidated the parts to be misunderstood calling them ‘the slippery spots’. Al-Atufi dedicated his Hashiya on al-Kashshaf to Suleiman. Öz Atûfî, Bayezid, Selim ve Süleyman Han devirlerine şâhid olmuş, özellikle Bayezid döneminde sarayda muallimlik yapmış, hayatının önemli bir bölümünde İstanbul camilerinde Cumâ günleri tefsir dersleri yaparak irşâd faaliyetinde bulunmuş ve 948/1541’te yine İstanbul’da vefat etmiş, Merzifon doğumlu önemli bir âlimdir. Tefsir’den Hadis’e, Tıbbu’n-Nebevî’den rüyâ tâbiri ve mantık ilmine kadar birçok alanda şerhi bulunan Atûfî’nin tefsîre dair üç şerhi, bir de müstakil ayet tefsiri vardır. Bunlar, “Hâşiye ale’l-Keşşâf” (Nebe’den Nâs’a), “Hâşiyetün ala Envâri’t-Tenzîl li’l-Beydâvî”, Beydâvî’nin bir ayet tefsirini şerheden “Risale fi Beyâni Tefsîr-i Kavlihî Teâlâ - Fe-Suhkan” ve müstakil bir ayet tefsiri olan “Hısnü’l-Âyati’l-Izâm fî Tefsiri Evâili Sûreti’l-En’âm” isimli eserdir. Özellikle meânî ve beyân ilmini şerhlerinde etkin bir şekilde yansıtan Atûfî, Sebeb’ten müsebbibe giden yolun lugavî, nahvî ve belâgatla ilgili inceliklerini şerhlerinde sergilemiştir. Bu makalenin inceleme konusunu olan Keşşâf hâşiyesinde de benzer özellikleri ziyâdesiyle görülmüştür. Zemahşerî’nin yeterince açıklamadığı kelime ve cümlelere yoğunlaşan şerhleri, bazen eleştiri dilini de kullanmıştır. Tefsirde Nesefî ve Beydâvî gibi meşhur müfessirlerin görüşlerinden, lügavî alanda Ferra, Sekkâkî, İbn Cüreyc’den, rivayet konusunda da çoğunlukla İbn Abbas, Mukâtil’den istifade etmiştir. Zemahşerî’nin başka alimlerden naklettiği bazı görüşleri de dilbilimi kapsamında eleştirmiştir. Zemahşerî’yi haşiye süresince müsannif olarak ifade eden, görüşlerini “kavlühü” diyerek nakleden müfessir, Zemahşerî’nin üslûbundan esinlenerek “fenkale” tarzını da şerhinde kullanmıştır. Zemahşerî’nin itikâdî görüşlerine imkan nisbetinde girmeyen Atûfî, açıklama gereği hissettiği konuları bir “tetimme” başlığı altında kaleme almıştır. Nebe ile Nas arasındaki sûrelerin tefsirinin şerhi esnasında “Mezâliku’l-Mahal” dediği yanlış anlaşılabilecek kısımlara ağırlık vermiştir. Şiiri seven, şiirden istişhatta bulunan müellif, Keşşâf hâşiyesini Sultan Süleyman’a ithaf etmiştir.